Literatura e cultura em Feira de Santana: práticas, usos e tendências em impressos da Folha do Norte (1951-1969) - Santos, Grazyelle Reis dos (2008)
In this work, a study is made on the practices, uses and tendencies of literature – chronicles, letters, story and poems – produced by writers from Feira de Santana that published on the local weekly magazine Folha do Norte, from 1951 until 1969, a period remarkable for its rapid changes on the urban environment and the socio-cultural view of this city. Investigation were done on the means these writers articulated themselves, their means of association and projects for cultural creation, taken from information found in Folha do Norte. Other information allowed a study on the dynamic of the cultural activities in the field of languages and arts, in the same period, such as book releases and events with such purpose. From the collection of 1298 productions contained in the newsletter in 20 years, a particular emphasis was made on the literary works themed after the city, Feira de Santana. It was observed and worth noting that the representation of a “prosperous town” was the tone of many speeches, literary or not, as if stating, symbolically, a social and cultural supremacy in comparison to other cities from the countryside of Bahia. It is pondered, on this context of representations, the political-ideological perspective adopted by the Folha do Norte, main journal on circulation within Feira de Santana. Methodologically, this research is the result of qualitative analysis on the literature produced by the city’s writers and from data identified on the issues treated by the newspaper. The concept of “representação” (Chartier, 1992) is fundamentally important for this study, even more for analyses of the disputes and interests involved in the discursive process of the elaboration and diffusion of ideas. Following the theoretic line of the “New Cultural History” and “Cultural Studies” and mixing History with Literature, resulting in the social history of literature and culture on Feira de Santana in the 1950’s and the 1960’s. This research had the backing of the Fundação de Amparo à Pesquisa do Estado da Bahia, together Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – FAPESB/CAPES.